2011
DOI: 10.1088/0957-4484/23/1/015705
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of hydrogen with ZnO nanopowders—evidence of hydroxyl group formation

Abstract: There have been many investigations to reveal the nature of the hydrogen gas and ZnO nanopowder interaction at elevated temperatures, while at present no conclusive description of such an interaction has been confidently reported. In this work, we demonstrate that a hydroxyl group is formed during this interaction, depending on size and relative crystallinity of nanopowders. Our in situ Raman spectroscopy investigations show that the interaction directly affects the intensity of the Raman signal at 483 cm(-1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 45 publications
4
26
0
Order By: Relevance
“…These observations suggest that adsorbed H atoms can reduce the surface and extract lattice O atoms to yield H 2 O. This step is consistent with formation of surface OH species from adsorbed H that has been observed through vibrational spectroscopies and linked to H 2 O formation from ZnO [19][20][21].…”
Section: Mechanism Of Ch 3 Ch 2 Oh Decomposition On Zno 1 100 ð þsupporting
confidence: 85%
“…These observations suggest that adsorbed H atoms can reduce the surface and extract lattice O atoms to yield H 2 O. This step is consistent with formation of surface OH species from adsorbed H that has been observed through vibrational spectroscopies and linked to H 2 O formation from ZnO [19][20][21].…”
Section: Mechanism Of Ch 3 Ch 2 Oh Decomposition On Zno 1 100 ð þsupporting
confidence: 85%
“…It can be seen that the E 2 ‐high peak appears at 568.9 cm −1 after 20 min of the low‐temperature nucleation (Stage 1), corresponding to a stress‐free state . A minor peak at 549.3 cm −1 is also observed in the same spectra, which is ascribed to the signal from the ZnO nanorods . The GaN phonon peak then shifts to lower wavenumbers with increased layer thickness, indicating the buildup of tensile stress as the lateral coalescence of GaN proceeds among the nanorods.…”
mentioning
confidence: 89%
“…It must be noted that as of today, the existence of this reaction has not been proven. It has been reported that H2 can undergo homolytic dissociation on dry surfaces [88][89][90] but this process has yet to be observed in aqueous chemistry.…”
Section: H 2 / Omentioning
confidence: 99%